Not dead yet: Three takes on auteurism in contemporary French and Francophone cinema. (August 2014) - Burgin, Alice; McGregor, Andrew; Nettelbeck, Colin
Sixty years have passed since the term une politique des auteurs was first coined by François Truffaut in the pages of Les Cahiers du cinéma . Initially an approach to filmmaking reacting against its own socio-political context, la politique evolved into something of an ideological celebration of the personal worldview of the artist, and became a dominant element in determining a new canon of cinéma d'art . Since the fall of the French colonial empire, the end of the Cold War and the rise of a vastly transformed global order, the French cinema industry, including many historians and critics, seems to have largely maintained the auteur-based model in terms of its funding and self-projection on both a national and an international level. But is that not an anomaly? What is the real place and meaning of the auteur paradigm within the context of a diverse and fractured Francophone world? This article provides three different perspectives regarding the critical purchase of la politique des auteurs within the contemporary postcolonial Francophone cinematic landscape. Through these perspectives, we argue that while the auteur paradigm can claim relevance within the confines of the Franco-French film industry, its wider applicability as a model for Francophone filmmaking raises pertinent questions about the continuing influence of the metropolitan centre on how minority identities are constructed and received.